The Role of Internal Work Environment Dimensions in Reducing Job Burnout – Field study on Administrative Staff in Jeddah University – - Alghamdi, Laila Ail Metab; Alshamasi, Areej Abdulrahman (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to identify the role of the internal work environment dimensions represented in (Leader-member exchange, Member-member exchange, management leader, incentives, administrative communication and material components) in reducing job burnout among the administrators at the University of Jeddah. In addition, it aimed to identify the degree of job burnout among administrators at the University of Jeddah, and detect which of the dimensions of the internal work environment has a greater degree of contribution to job burnout among administrators at the University of Jeddah. The descriptive and analytical approach was used. In order to achieve the objectives of the study, a questionnaire containing of (45) phrases was designed as a tool for data collection. The study' population was made up of all the administrative workers at the University of Jeddah, whose number is (1088) administrator. A simple random sample was chosen from the study population, whose number reached (276) administrator. The data were processed statistically using the (SPSS) program. Several results were reached, the most important of which are: the existence of a negative impact of the internal work environment dimensions on job burnout of administrators at the University of Jeddah, except for the dimension of (incentives). The results showed that there was no effect of this dimension on job burnout. The level of the existence of job burnout was of a moderate degree of (65.3%). The (management leadership) dimension had a greater contribution to job burnout among administrators at the University of Jeddah. In light of the results, the study recommended several recommendations, the most important of which are: the necessity to hold an awareness-raising program at the university to educate the administrators about the seriousness of the phenomenon of job burnout and methods of treatment in order to limit its spread. In addition, the necessity to create effective communication channels to allow communicating the suggestions and complaints of the administrators to the university's senior management to facilitate identification of the causes of job burnout among administrators.
Keywords: internal environment; work relationship; administrative leadership; incentives; administrative communication; job burnout